Proton Exchange Membrane Fuel Cell (PEMFC) and Its Prospect for Powering Automobile in the Future: A Review - Nashira*, Alimatun; Asyifa, Soniya Nur; Yosida, Riski Sindi (Graduate School of Universitas Syiah Kuala, 2022)
Increasing responsibility toward the environment forced the transportation sector to shift its gear toward electric vehicles. While battery electric vehicle (BEV) has started enjoying success, it poses a question as to whether or not fuel cell vehicle (FCV) becomes redundant even before being widely deployed. The commercialization of FCV usually only comes after a long period after the prototype was introduced, signifying certain barriers to large-scale utilization. Aside from the various LCAs, studies have also tried to estimate the future cost and model FCV adoption. Due to the limited data and different regional conditions in which the project was done, these researches used vastly different scenarios and assumptions, making the result differ significantly. The lack of a clear-cut answer might indicate that the fate of FCV is not yet decided, and the PEMFC might still play a part in the green transportation era, albeit not as the dominant technology. Alternative uses and the condition required to utilize them were discussed in this short review.